Pseudotumoral ovarian disorders. Experience in Jauja, Peru - Reymundo, Gabriela (2015)
OBJECTIVES: To study the incidence of pseudotumoral disordes, including ovarian cysts in Jauja and towns of influence of Domingo Olagevoya Hospital. DESIGN: Retrospective study of clinical histories, 1986-1995. LOCATI0N. Jauja's Domingo Olavegoya Hospital. RESULTS. Age 20 to 40 year-old represented 63,6%. Patients were mainly from jauja in 47,7% and urban group in 47,5%. Duration of disease was one month to one year, with variable symptomatology. Most frequent localization was the right ovary in 65,9%; 45,4% received medical treatment and 40,9% underwent surgery. CONCLUSIONS: Ovarian cysts are the most frequent pseudo tumoral disordes, mainly in the group 20 to 40 year-old. The majority of patients require only medical treatment and surgical therapy is reserved to specific cases.